Optimization of Application use Microsoft Office Excel Based for Student Data Management - Suwatri Suwatri; Rahmat Suryanto (Universitas Lampung, 2021)
So far, in managing student data in schools using manual methods, the work becomes difficult, ineffective and takes a long time. The many types of student data that must be created by schools make schools strive to manage student data that is practical and stored digitally. By optimizing the use of student administration applications based on Microsoft Office Excel, it is hoped that it can provide convenience in managing student data in schools, especially helping to facilitate the work of administrative staff and teachers in schools. This research was conducted through interviews with several schools which were used as research objects to use student administration applications. The study was conducted in several schools in the Pesawaran district of Lampung province in the 2019/2020 school year. After the school optimizes the use of Microsoft Office Excel-based student administration applications, the management of school student data is organized effectively, practically, doesn't take long, and the data is stored digitally neatly. Keywords: Optimization, Excel MO-based Applications, Student Data ManagementDOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202102